GRAD U ROMANU VJEŽBANJE ŽIVOTA NEDJELJKA FABRIJA (Filološke pripombe, 2019)
The paper considers the issue of multiculturalism in Nedjeljko Fabrio’s novel Practising Life, as well as the possibilities of intercultural dialogue between oppositional groups through the prism of an urban space. The emphasis is primarily placed on the complex representation of an urban space in the novel, where the author's representation of the city is actually twofold since the city is viewed both as a physical reality and a cultural construct. According to Richard Lehan, urban constructs must constantly be reexamined because they are artificial and diverse, and through them one can interpret (and reinterpret) past and our sense of reality. Thus, Fabrio in a distinctive way shows how effects of commercial and industrialized processes transform the city and relations among people and also affect political developments in it because, at the same time, the capital is in an unbreakable connection with the dominant political tendencies.